2006
DOI: 10.1109/tro.2006.875492
|View full text |Cite
|
Sign up to set email alerts
|

Macro-continuous computed torque algorithm for a three-dimensional eel-like robot

Abstract: Abstract-This paper presents the dynamic modeling of a continuous three-dimensional swimming eel-like robot. The modeling approach is based on the "geometrically exact beam theory" and on that of Newton-Euler, as it is well known within the robotics community. The proposed algorithm allows us to compute the robot's Galilean movement and the control torques as a function of the expected internal deformation of the eel's body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
147
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 26 publications
0
147
0
7
Order By: Relevance
“…In order to support this idea, we consider an underwater snake robot described by (3) forced to move with lateral undulation, (5), and eel-like motion, (6), along the global x axis with φ 0 = 0 o . Fig.…”
Section: Analysis Of Link Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to support this idea, we consider an underwater snake robot described by (3) forced to move with lateral undulation, (5), and eel-like motion, (6), along the global x axis with φ 0 = 0 o . Fig.…”
Section: Analysis Of Link Motionmentioning
confidence: 99%
“…Empirical and analytic studies of snake locomotion were reported by Gray [3], while, among the first attempts to develop a snake prototype, the work of Hirose [4] is essential. Recently, HRMs are presented that are suited for aquatic propulsion as well [5], [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been noted in the bio-robotics community, underwater snake robots bring a promising prospective to improve the efficiency and maneuverability of next generation underwater vehicles [1,11,30]. They have several promising applications for underwater exploration, monitoring, surveillance and inspection, and they carry a lot of potential for inspection of subsea oil and gas installations.…”
Section: Introductionmentioning
confidence: 99%
“…In [11,12], the authors propose a model of underwater snake robots, where the dynamic equations are written in closed form. Compared to the models in [1,4,21,24,27,30] it is an advantage from an analysis point of view that the model is in closed form, as opposed to including numerical evaluations of the drag effects. In addition, it is beneficial that it includes both resistive and reactive fluid forces, since swimming snake robots operate at Reynolds numbers that require both these effects to be taken into account.…”
Section: Introductionmentioning
confidence: 99%